New anticancer medicines approved by the EMA in 2024 - Bege, Miklós; Borbás, Anikó (De Remediis, 2025)
Tumorous diseases are among the leading causes of death in the developed world, therefore there is a constant need for new antineoplastic medicines. In 2024, the EMA approved 28 anticancer drugs, of which 13 contains new active substances. In this review, we briefly summarize the mechanism of action and use of the new drugs approved by the EMA.